Serotyping and bacteriophage typing of human and bovine group-B streptococci - HAUG, RANGDI HOLTH; GUDDING, R; BAKKEN, G (Journal of medical microbiology, 1981)
Norwegian Defence Microbiological Laboratory, Oslo * National Veterinary Institute, Oslo, Norway Received January 26, 1981 Accepted April 23, 1981 SUMMARY. Serotypes and phage types of group-B streptococci isolated from healthy and diseased human subjects and from cattle in different parts of Norway have been compared. The phage set used was found to be suitable for the study of strains from cows as well as from man.